2021
DOI: 10.3390/metabo11020111
|View full text |Cite
|
Sign up to set email alerts
|

The Acute Effects of Swimming Exercise on PGC-1α-FNDC5/Irisin-UCP1 Expression in Male C57BL/6J Mice

Abstract: Irisin is a myokine primarily secreted by skeletal muscles and is known as an exercise-induced hormone. The purpose of this study was to determine whether the PGC-1α -FNDC5 /Irisin-UCP1 expression which is an irisin-related signaling pathway, is activated by an acute swimming exercise. Fourteen to sixteen weeks old male C57BL/6J mice (n = 20) were divided into control (CON, n = 10) and swimming exercise groups (SEG, n = 10). The SEG mice performed 90 min of acute swimming exercise, while control (non-exercised… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Therefore, SA/JA antagonism may play a role in the outcome to PWN inoculation in P. pinaster , with the activation of SA pathway in susceptible plants and JA pathway in resistant ones, at 72hpi. In a recent study where hormone levels were analyzed for another P. pinaster family described in Carrasquinho et al ( 2018 ), high levels of SA and jasmonic acid methyl ester (JA-ME) were detected in susceptible plants at 72 hpi (Rodrigues et al, 2021 ), supporting an important role for SA in PWN susceptibility. In P. thurnbergii , the induction of JA and SA responsive genes was also observed in susceptible plants (Hirao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Therefore, SA/JA antagonism may play a role in the outcome to PWN inoculation in P. pinaster , with the activation of SA pathway in susceptible plants and JA pathway in resistant ones, at 72hpi. In a recent study where hormone levels were analyzed for another P. pinaster family described in Carrasquinho et al ( 2018 ), high levels of SA and jasmonic acid methyl ester (JA-ME) were detected in susceptible plants at 72 hpi (Rodrigues et al, 2021 ), supporting an important role for SA in PWN susceptibility. In P. thurnbergii , the induction of JA and SA responsive genes was also observed in susceptible plants (Hirao et al, 2012 ).…”
Section: Discussionmentioning
confidence: 94%
“…Bursaphelenchus xylophilus isolate Bx013.003 (Carrasquinho et al, 2018 ; Rodrigues et al, 2021 ) was obtained from an infested field tree exhibiting wilting symptoms in central Portugal (39°43′33.8 ′′ N, 9°01′55.7 ′′ W) and was included in the collection of INIAV's Nematology Laboratory, Oeiras, Portugal. The sequence of the ITS region is available at GenBank (NCBI) under the accession number MF611984.1 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we did not measure circulating FGF21 and irisin concentrations in blood of mice. Although it is a significant shortcoming of our data, previous studies reported that the increase of blood FGF21 and irisin concentrations by exercise are accompanied by the increase of FGF21 and FNDC5 contents of skeletal muscle (Cho et al, 2021;Tanimura et al, 2016). Therefore, we guessed that the increase of FGF21 contents of skeletal muscle is involved in the browning of WAT.…”
Section: Adipose Tissue Browning-related Proteins In Skeletal Musclementioning
confidence: 76%
“…Therefore, acute exercise may regulate the expression of PGC-1α and Ucp1 to achieve browning of WAT. Eunhee C et al [ 57 ] showed that 90 min of acute swimming exercise could lead to increased expression of the Fndc5 gene and protein in soleus muscle and increased Fndc5 protein in gastrocnemius muscle. Consistently, the protein expression of Ucp1 was increased in scWAT.…”
Section: Effects Of Different Exercise Programs On Promoting the Browning Of Watmentioning
confidence: 99%